miR-100-5p is upregulated in multiple myeloma and involves in the pathogenesis of multiple myeloma through targeting MTMR3 - Xiaofang Wei; Youfan Feng; Yuan Fu; Fei Liu; QiaoLin Chen; Wenjie Zhang; Yangyang Zhao; Xiujuan Huang; Yang Chen; Qingfen Li; Qike Zhang (Hematology, 2023)
ABSTRACTObjectives: MicroRNA (miRNA) is a kind of highly conserved single-stranded small endogenous non-coding RNA associated with multiple diseases, particularly cancer. The miRNAs expression profile in multiple myeloma (MM) has been barely elucidated.Methods: The miRNAs expression profiles in bone marrow plasma cells of 5 MM individuals and 5 iron-deficiency anemia volunteers were analyzed using RNA-sequencing. Quantitative polymerase chain reaction (QPCR) was performed to validate the expression of selected miR-100-5p. The biological function of selected miRNA was predicated by bioinformatics analysis. Finally, the function of miR-100-5p and its target on MM cells were evaluated.Results: MiRNA-sequencing showed that miR-100-5p was obviously upregulated in MM patients, which was further validated in an expanded cohort. Receiver operating characteristic curve analysis characterized miR-100-5p as a valuable biomarker of MM. Bioinformatics analysis predicted that miR-100-5p is targeted to CLDN11, ICMT, MTMR3, RASGRP3, and SMARCA5, and their low expression are associated with poor prognosis of MM patients. Kyoto encyclopedia of genes and genomes analysis suggested that the major interacting proteins of these five targets are mainly enriched in inositol phosphate metabolism and phosphatidylinositol signaling system pathway. In vitro study showed that miR-100-5p inhibition promoted the expression of these targets, especially MTMR3. In addition, miR-100-5p inhibition declined living number and metastasis, whereas promoted apoptosis of RPMI 8226 and U266 MM cells. The function of miR-100-5p inhibition was weakened by MTMR3 inhibition.Conclusion: These results indicates that miR-100-5p is a promising biomarker for MM, and that it may involve in the pathogenesis of MM by targeting MTMR3.